2010
DOI: 10.1227/01.neu.0000371971.51755.1c
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trait Anxiety in Persistent Radicular Pain After Surgery for Lumbar Disc Herniation

Abstract: The presence of trait anxiety before surgery is a prognostic factor for the persistence of pain after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Although most studies used regression analyses to test prediction models of outcomes, two studies used discriminant analysis [18,19] and one used cluster analysis [23]. Six studies included an adjustment for baseline leg pain, back pain, or functional disability in their prediction models [19,21,24,27-29], while five studies had an adjustment for other variables [17,20,22,25,26]. One study was originally a randomized clinical trial that did not find a significant difference between two rehabilitation programs [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most studies used regression analyses to test prediction models of outcomes, two studies used discriminant analysis [18,19] and one used cluster analysis [23]. Six studies included an adjustment for baseline leg pain, back pain, or functional disability in their prediction models [19,21,24,27-29], while five studies had an adjustment for other variables [17,20,22,25,26]. One study was originally a randomized clinical trial that did not find a significant difference between two rehabilitation programs [26].…”
Section: Resultsmentioning
confidence: 99%
“…Two (one high and one low quality study) of the four studies that measured pain coping preoperatively reported association with postoperative outcomes [18,24]. The two studies (one high and one low quality studies) that measured anxiety found an association with LDH surgical outcomes [17,25]. Three (high quality studies) out of four studies that measured fear and avoidance beliefs found an association with LDH surgical outcomes [19,24,26].…”
Section: Resultsmentioning
confidence: 99%
“…The MBMD survey has not been validated for TMD and the TMD population could represent a unique group in whom chronic anxiety predominates compared with the other psychological factors. Preoperative chronic anxiety has been shown to predict the magnitude of postoperative pain after oral and maxillofacial surgery, 25,26 orthopedic surgery, 27-32 neurosurgery, 33 oncology, 34,35 and general surgery. [36][37][38] The actual nature of the surgical procedure does not appear to influence the effect of chronic anxiety on the magnitude of postoperative pain decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for pre-surgical distress is likely to identify patients at risk for poor outcome after surgery (26). Presence of trait anxiety before surgery is a prognostic factor for the persistence of pain after surgery (27). The 3 studies described above investigated patients 1 year after surgery.…”
Section: Discussionmentioning
confidence: 99%